El Greco's Portrait of Giulio Clovio as Creator: an Artistic Affinity and Assertion of Creative Identity - (:unkn) unknown (My University, 2015)
EL GRECO’S PORTRAIT OF GIULIO CLOVIO AS CREATOR: AN ARTISTIC AFFINITY AND ASSERTION OF CREATIVE IDENTITY by Jordan M. Severson The University of Wisconsin-Milwaukee, 2015 Under the Supervision of Professor Tanya Tiffany In 1571, Domenikos Theotokopoulos of Crete, today remembered as El Greco, painted a spectacular portrait of the manuscript illuminator Giorgio Giulio Clovio while in Rome. In this portrait, El Greco commemorated Clovio and his work by depicting him with his most praised creation, The Farnese Hours. Despite the portrait’s renown, scholars have generally only mentioned it in larger studies of portraiture or in comparison to El Greco’s other works. It has been examined primarily for its value as a likeness with little attention to its deeper implications or context. However, the image is rich with content more complex than any typical portrait. The image bears unexplored connections to a time of El Greco's burgeoning intellectual and theoretical understanding while containing references to the status of the artist and the very act of creation. This study analyzes Clovio’s portrait in conjunction with key primary sources, such as Pacheco’s treatise on painting and El Greco's own annotations, along with recent scholarship on El Greco to elucidate the manner in which the image deviates from typical portraiture of the time. This examination brings much needed focus and contextualization to the portrait and considers its stylistic details along with the relationship between Giulio Clovio and El Greco. Furthermore, this analysis presents the intellectual, nuanced details of the portrait in context to show how El Greco manipulated artistic conventions to suit his own unique purposes. This study considers the Clovio portrait within Richard Brilliant’s theoretical framework for portraiture, in regards to the portrait’s qualities beyond the normal expectations of portraits in Renaissance Italy. The implications of this perspective reveal much about the development of El Greco's artistic thought and practice while he lived in Rome.
Keywords: Alessandro Farnese; El Greco; Fulvio Orsini; Giulio Clovio; Portraiture; Rome